Enhancement of learning experience using skill-challenge balancing approach - Katuk, Norliza; Wang, Ruili; Ryu, Hokyoung (Springer Berlin Heidelberg, 2011)
This paper addresses the issue of content sequencing in computer-based learning (CBL).In doing so, it proposes a Skill-Challenge Balancing (SCB) approach as a way to enhance the CBL experience. The approach is based on the Flow Theory, allowing self-adjustment of the given levels of challenges in a given learning tasks so that the learner will consistently be adaptively able to engage in the CBL activity.An empirical study with 70 students suggested that the SCB-based learners were significantly better in their learning experience specifically in their focus of attention and intrinsic interests compared to the learners in the system without SCB.The results also revealed that SCB was fully utilised by the learners to regulate the levels of difficulty of the CBL tasks.